159k views
4 votes
For f(x) = 3x+ 1 and g(x) = x2 - 6, find (f+g)(x).

O A. 3x3 - 5
O B. x+3x-5
O c. x+3x+7
O D. 3x - 17
SUBMIT

User Ryan Doom
by
5.5k points

2 Answers

2 votes
your answer would be option B. x+3x-5
User Papey
by
4.9k points
2 votes

Answer:

B. x² + 3x - 5

Explanation:


(f+g)(x)=f(x)+g(x)\\\\\text{Substitute}\ f(x)=3x+1,\ g(x)=x^2-6:\\\\(f+g)(x)=(3x+1)+(x^2-6)\qquad\text{combine like terms}\\\\(f+g)(x)=x^2+3x+(1-6)\\\\(f+g)(x)=x^2+3x-5

User Kyle
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.